The effect of an Olympic distance triathlon on the respiratory muscle strength and endurance in triathletes - Boussana, A.; Galy, O.; Le Gallais, D.; Hue, O. (Journal of Exercise Rehabilitation, 2020)
High-intensity exercise, marathons, and long distances triathlons have been shown to induce the fatigue of respiratory muscles (RMs). Nevertheless, fatigue and the recovery period have not been studied in response of an Olympic distance triathlon (1.5-km swim, 40-km bike, 10-km run: short-distance triathlon). The aim of this study was to evaluate the RM fatigue induced by an Olympic distance triathlon. Nine male triathletes (24± 1.1 years) underwent spirometric testing and the assessment of RM performance. Respiratory function tests were conducted in sitting position. Spirometric parameters, maximal inspiratory and expiratory pressures, and RM endurance assessed by measuring the time limit were evaluated before (pre-T), after (post-T), and the day following the triathlon (post-T-24 hr). Residual volume increased: pre-T vs. post-T (P< 0.002), maximal inspiratory pressure significantly decreased from 127.4± 17.2 (pre-T) to 121.6± 18.5 cmH2O (post-T) (P< 0.001) and returned to the pre-T value 24 hr after the race (125.0± 18.6). RM endurance significantly decreased from 4:51± 0:8 (pre-T) to 3:13± 0:7 min (post-T, P< 0.001) and then remained decreased for 24 hr after the race from 4:51± 0:8 (pre-T) to 3:39± 0:4 min 24 hr after (P< 0.002). Both, strength and endurance of inspiratory muscles decrease after Olympic distance triathlon. Furthermore, the impaired of inspiratory muscle endurance 24 hr after the race suggested a slow recovery and persistence of inspiratory muscle fatigue.